Peran Pendidikan Islam dalam Melestarikan Nilai-Nilai Budaya Lokal - Awaliah, Fuji; Santosa, Sedya (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Islamic education has an important role in shaping individual and collective character and strengthening local cultural identity in the current era of globalization. the role of Islamic education in promoting local customs. This study uses a qualitative approach with a type of library research to explore the role of Islamic education in preserving local culture. The results show that the development of educational programs based on local culture can be one of the solutions to strengthen cultural identity among students. Some madrasahs and pesantren have implemented project-based learning that involves students in cultural preservation activities, such as research on local history, making traditional artworks, or documenting folklore. Community involvement in educational activities, such as cultural festivals and tradition celebrations, further strengthens the relationship between education and local culture. Islamic education has the potential to create a generation that not only has a strong understanding of religion, but also a rich cultural identity, so that it can contribute positively in maintaining and developing the richness of local culture in the midst of changing times.